Baseline resistance associated substitutions in HCV genotype 1 infected cohort treated with Simeprevir, Daclatasvir and Sofosbuvir in Brazil - Aguiar, Bruna Forte; Campos, Guilherme Rodrigues Fernandes [UNESP]; Rodrigues, João Paulo Vilela; Marques, Nayara Nathie [UNESP]; Molina, Bárbara Floriano [UNESP]; Bittar, Cintia [UNESP]; Souza, Fernanda Fernandes; Martinelli, Ana de Lourdes Candolo; Rahal, Paula [UNESP]; Pereira, Leonardo Régis Leira (My University, 2019)
Background: The World Health Organization estimates that 1% of the world population (71 million) is infected with hepatitis C virus (HCV). In 2015, three direct-acting antivirals (DAAs), simeprevir (SMV), sofosbuvir (SOF) and daclatasvir (DCV) were included in the Brazilian protocol for the treatment of chronic hepatitis C. Despite the fact that the use of these drugs is associated with higher treatment response rates and with lower incidence of side effects, studies have shown the association between the presence of viral resistance mutations and the failure of pharmacological treatment. Aim: This way, this study aimed to evaluate the safety and effectiveness of treatment for HCV genotypes 1a and 1b infected patients with these DAAs, also analyzing the occurrence and prevalence of baseline resistance associated substitutions (RAS), observing the impact of these mutations into the treatment success. Methods: Clinical data were collected from all the 262 HCV infected patients included for comparative analysis, while serum samples collected from 144 of these individuals, before treatment, were submitted to molecular biology approaches for mutation analysis into NS3, NS5A and NS5B regions. Results: Regarding the treatment regimens, 49.6% of the patients received SOF + DCV ± ribavirin and 50.4% used SOF + SMV ± ribavirin. The sustained virological response at 12 weeks post-treatment (SVR12) rate was 92.7% (93.9% for SOF plus DCV and 91.7% for SOF plus SMV). No clinical or laboratorial factor was statistically associated with SVR. The most common adverse reactions were haematological events, nausea/vomiting, headache and asthenia. Out of 144 blood samples, 70 (48.6%) had detected RAS, 34.8% treated with SOF + DCV ± ribavirin and 61.3% SOF + SMV ± ribavirin. The resistance mutations against SMV were detected into NS3: substitutions G122S (28%), I170V (22.7%), Y56F (17.3%) and V132I (14.7%). The mutations against DCV R30Q (9.1%), P58H (6.1%) and Q62E (6.1%) were observed into NS5A, and for SOF the mutations A421V (10.6%), L159F (6.4%) and C316N (6.4%) were present inside NS5B viral protein. Four patients did not reach SVR, three of them presented viruses carrying RAS (1 treated with SOF + DCV and 2 with SOF + SMV). Some of these mutations, like R30Q (present in relapsing samples) and L159F, are well known by their influence on antiviral resistance, while others, like C316N, have a compensatory effect on viral fitness, maintaining these baseline RAS. Conclusion: The use of treatment regimens composed of SOF and DCV or SOF and SMV showed a high SVR rate, despite of a high rate of RAS, and a good tolerability profile in patients with HCV genotype 1. However, the high occurrence of baseline RAS observed in this casuistic is still a concern and studies like this show the necessity to understand how they are maintained in the population and to direct more efficiently the use of DAAs.
Keywords: Antiviral resistance; Baseline mutations; DAA treatment; Genotype 1; HCV